1997
DOI: 10.1021/ie960724c
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Kinetics and Mechanisms of Hydrocarbon Thermal Cracking:  An Ab Initio Approach

Abstract: Unrestricted Hartree-Fock and density functional theory calculations have been carried out to investigate the detailed kinetics and mechanisms of hydrocarbon thermal cracking. The calculations of the elementary reactions involved in the overall cracking of paraffin molecules agree well with the generally accepted free radical mechanism. The results can be summarized as follows: (1) Initiation cracking, the calculated bond dissociation energy (BDE) for C-C homolytic scission is ∼95 kcal/mol at the MP2/6-31G* le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…Since the bonds in hydrocarbons are very energetic (CC, ∼350 kJ/mol and CH, ∼410 kJ/mol) 22 cracking can take place only at high temperatures. Once radicals have formed, the subsequent reaction steps towards the decomposition of the molecule should take place 23. Accordingly, having low energy bonds such as the CO epoxide (∼280 kJ/mol) in cyclopentene oxide 24 is expected to enhance radical formation allowing the precursor to decompose at lower temperatures than with saturated and aromatic hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…Since the bonds in hydrocarbons are very energetic (CC, ∼350 kJ/mol and CH, ∼410 kJ/mol) 22 cracking can take place only at high temperatures. Once radicals have formed, the subsequent reaction steps towards the decomposition of the molecule should take place 23. Accordingly, having low energy bonds such as the CO epoxide (∼280 kJ/mol) in cyclopentene oxide 24 is expected to enhance radical formation allowing the precursor to decompose at lower temperatures than with saturated and aromatic hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we examine the applicability of ab initio quantum chemical calculations to obtain quantitative kinetic and thermodynamic data for hydrocarbon radical reactions (Heuts et al, 1996;Xiao et al, 1997;Mayer et al, 1998;Marsi et al, 2000;Sumathi et al, 2001aSumathi et al, ,b, 2002. We focus on reactions that occur during the steam cracking of hydrocarbons, though hydrocarbon radical reactions play an important role in many other chemical processes as well, ranging from atmospheric reactions to industrial processes such as combustion, polymerization, and polymer degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The ever-increasing computational power and the development of better algorithms bring the accurate calculation of kinetic and thermodynamic parameters for industrially relevant gas-phase reactions from first principles within reach. Hydrocarbon free-radical reactivity and thermochemistry have been studied with a variety of computational methods, ranging from semiempirical to density functional theory (DFT) and postHartree-Fock methods (Wong et al, 1994;Barone and Orlandini, 1995;Heuts et al, 1996;Xiao et al, 1997;Wong and Radom, 1998;Blowers and Masel, 2000;Chuang et al, 2000;Stahl et al, 2001;Sumathi et al, 2001aSumathi et al, ,b, 2002. It is found that in order to obtain results with so-called chemical accuracy for standard enthalpies of formation, that is, better than 4 kJ/mol, calculations on radical species and on radical reactions require large basis set post-Hartree-Fock methods (Mayer et al, 1998;Chuang et al, 2000;Saeys et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ab initio quantum chemistry has long been applied as a major tool for investigating the structure, stability, reaction kinetics and mechanisms of different molecular systems [14][15][16][17][18][19][20][21][22][23]. Blaszkowski et al studied ethane conversion reactions using local density approximation (LDA) calculations, a low level density functional method [12].…”
Section: Introductionmentioning
confidence: 99%